Dimensional Analysis, Thermodynamics and Conservation Laws in a Problem of Radiation Processes Simulation - Ivanov, M. Ja.; Zestkov, Grigori B. (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
The mathematical modeling in radiation processes, based on experimental data of modern physics and traditional approaches of dimensional theory, thermodynamics and gas dynamics is considered. Dimensional analysis allows predicting important characteristics of radiation process (mass of particles-bosons radiation, the magnitude of the radiation pressure, the characteristic linear dimensions), and also indicate the possibility of superluminal motion (without the violating the principle of causality). Methods of thermodynamics lead to the refined modeling of equilibrium radiation, the equation of state of radiation protection, determine the heat capacity and the value of radiation pressure in the source. A gas dynamics approach to formulate a closed system is thermodynamically consistent conservation laws for radiation heat-conducting gas. In this direction we present one-velocity two-temperature and one-temperature approximation. Demonstrate some practical applications of the methods of modeling.